A kinetic assay of total lipase activity for detecting lysosomal acid lipase deficiency (LAL‐D) and the molecular characterization of 18 LAL‐D patients from Russia. Issue 1 (3rd June 2019) - Mayanskiy, Nikolay; Brzhozovskaya, Ekaterina; Pushkov, Alexander; Strokova, Tatiana; Vlasov, Nikolay; Surkov, Andrej; Gundobina, Olga; Savostianov, Kirill
Abstract: Laboratory diagnostics of lysosomal acid lipase deficiency (LAL‐D), a rare disorder associated with LIPA alterations, are based on the evaluation of LAL activity. In dry blood spots (DBS) submitted for LAL‐D diagnostics (the screening cohort) over a two‐year period or obtained from a cohort of retrospective LAL‐D patients, we measured: (1) LAL activity using a two‐reaction assay with 4‐methylumbelliferone palmitate (4‐MU‐Palm) and Lalistat‐2, a specific LAL inactivator; (2) total lipase (TL) activity by a 1‐hour kinetic 4‐MU‐Palm cleavage reaction (no Lalistat‐2). The TL activity was expressed as the area under the kinetic curve after 1 hour (TL‐AUC1h ) of the reaction and presented as the median (min‐max). LAL activity was reduced in 30/537 individuals from the screening cohort, among which LIPA sequencing revealed six patients and one carrier. Overall, 16 (89%) individuals among six novel and 12 retrospective LAL‐D patients carried at least one c.894G>A mutation (six were homozygous). The TL‐AUC1h in nonLAL‐D specimens with normal LAL activity (n = 90) was unambiguously higher (9471 [4015‐23 585] RFU*h/punch) compared to LAL‐D patients, including six new and nine retrospective patients (1810 [357‐2608] RFU*h/punch). Importantly, in 13/15 examined nonLAL‐D specimens with reduced LAL activity the TL‐AUC1h was above a threshold of 2652 RFU*h/punch. Applying this threshold, the TL‐AUC1h index discriminated all LAL‐D patients (100% sensitivity) and 103/105 nonLAL‐D specimens (98% specificity). Given that there is no need for Lalistat‐2 and two parallel enzymatic reactions in conjunction with high sensitivity and specificity, the kinetic assay seems to be practical for LAL‐D screening. Synopsis: Lysosomal acid lipase deficiency responsible for Wolman disease and cholesterol ester storage disease could be reliably detected using a kinetic assay of total lipase activity with a fluorogenic substrate.